Hubungan Antara Prestasi Belajar dengan Perencanaan Karir - Sidik Apriansyah (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2014)
The learning achievement is an aspect that must be considered by the student, because it can affect career planning. Seeing this, the students are expected to have a maximum learning achievement. Reality is still a lot of students who have grades below a minimum completeness criteria (KKM). This study aims to determine the relationship between learning achievement in the career planning class XI student of SMAN 2 Bantul Academic Year 2014/2015. This research is a correlation, the variables of this study is twofold learning achievement variable (X) and career planning variable (Y). The population in this study is a class XI student of SMAN 2 Bantul Academic Year 2014/2015. The sample in this study a class XI student with the number of 37 students, pengembilan sample by random (random sampling). The collection of data on achievement variable learn to use data documentation, that the data value of report cards, and on career planning variables using a questionnaire. This validity test analysis using product moment formula, the analysis of the reliability test using Cronbach alpha formula, while data analysis using product moment formula. The results of this analysis demonstrate the value of the analysis of the correlation coefficient (r) between the variables of learning achievement of students with career planning amounted to 0.597 and p value 0.0000. Value of the determinant (r2) of 35.7%, so this shows that learning achievement contributes a positive and significant impact on student career planning, it can thus be concluded that: there is a positive and significant relationship between achievement of learning with career planning in class XI SMAN 2 Bantul Academic Year 2014/2015.